Transformative changes in human resources management practices in the tourism sector amidst the COVID-19 pandemic - Cizreliogullari, Mehmet Necati; Gunay, Tugrul; Kiroglu, Ugur (Journal of Tourism Management Research, 2024)
The COVID-19 pandemic has introduced a significant degree of uncertainty into the operational landscape of businesses within the tourism sector. These uncertainties have raised questions about how working conditions have evolved and may continue to change in the future. This phenomenon has not only had a widespread impact on the travel industry, but it has also extended its influence to the education sector, consequently affecting numerous other sectors in the broader economy. Within this context, the role of departments such as Human Resources (HR) has gained increasing prominence. These departments are entrusted with the crucial responsibility of monitoring workplace standards, particularly in terms of compliance with hygiene regulations and health procedures. The research was conducted in the accommodation service sector of Northern Cyprus (TRNC), encompassing businesses operating in various regions. A sample size of 20 was selected, with data collected from five different facilities situated across the Northern part of the island. This research seeks to shed light on the evolving landscape of human resources management practices in response to the transformative changes brought about by the COVID-19 pandemic. To achieve this objective, a qualitative research approach was employed. Oral interviews with business executives supplemented this strategy, giving the research findings more depth and context. The culmination of this study is presented in the final section, encapsulating the results and their implications. This research contributes to the ongoing discourse surrounding the impact of the COVID-19 pandemic on human resources, shedding light on the evolving landscape of work in the tourism sector.